2020
DOI: 10.33772/jumbo.v4i1.13260
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kesiapan Untuk Berubah Pada Karyawan Manufaktur: Analisis Praktek Kepemimpinan Di Masa Pandemi Covid-19

Abstract: This study aimed to measure the mediation effect of readiness for change between transformational leadership and employee performance relationship in a manufacture industry in Tangerang. Data collection was done by simple random sampling technique and the returned and valid questionnaire results were 195 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership have not significant effect on the employee performance, but transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on this situation, Covid-19 comes as a form of change in the work system in the medical record installation. Several studies have shown that employees who are ready to change tend to have high job performance (Asbari et al, 2021;Novitasari et al, 2020;Yuwono et al, 2020). Therefore, this study aims to assess the association between readiness to change and job performance of HIM professionals during the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this situation, Covid-19 comes as a form of change in the work system in the medical record installation. Several studies have shown that employees who are ready to change tend to have high job performance (Asbari et al, 2021;Novitasari et al, 2020;Yuwono et al, 2020). Therefore, this study aims to assess the association between readiness to change and job performance of HIM professionals during the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%